2020
DOI: 10.1002/mabi.202070005
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Living Cell Behavior with Ultra‐Low Fouling Polymer Brush Interfaces

Abstract: Front Cover: In article 1900351, Vaisocherová‐Lísalová and co‐workers investigate the structural properties of antifouling polymer brush surfaces for use as an efficient tool to control the behavior of living cells. It is shown that antifouling interfaces with a high content of zwitterionic moieties (>65mol%) modulate cell behavior completely differently compared to non‐ionic coatings. These differences are attributed mostly to the surface hydration capabilities. Image credit: https://Neuroncollective.com (Dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…A set of pCB brush coatings and OEG-based SAM coatings functionalized with variable concentrations of RGD peptides were prepared to investigate the effects of the RGD peptide-decorated antifouling background on mechanotransduction cell signaling. Based on our previous study [ 31 ], we used optimized biocompatible and highly hydratable antifouling pCB brush coatings with wet thicknesses around ~80 nm (characterized by spectroscopic ellipsometry; data not shown). Two different approaches to the preparation of the coatings functionalized with varying RGD concentrations were employed as follows: first, only carboxy-functional coatings of pCBAA or SAM of HS-(CH 2 ) 11 -(EG) 6 -OCH 2 -COOH were RGD-functionalized using immobilization solutions of RGD peptides of different concentrations ( Figure 1 A1,A2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A set of pCB brush coatings and OEG-based SAM coatings functionalized with variable concentrations of RGD peptides were prepared to investigate the effects of the RGD peptide-decorated antifouling background on mechanotransduction cell signaling. Based on our previous study [ 31 ], we used optimized biocompatible and highly hydratable antifouling pCB brush coatings with wet thicknesses around ~80 nm (characterized by spectroscopic ellipsometry; data not shown). Two different approaches to the preparation of the coatings functionalized with varying RGD concentrations were employed as follows: first, only carboxy-functional coatings of pCBAA or SAM of HS-(CH 2 ) 11 -(EG) 6 -OCH 2 -COOH were RGD-functionalized using immobilization solutions of RGD peptides of different concentrations ( Figure 1 A1,A2).…”
Section: Resultsmentioning
confidence: 99%
“…Hepatocytes are very sensitive cells [ 35 , 36 , 37 ], which makes them a good model system for mechanotransduction-signaling studies. Recently we showed that nonfunctionalized antifouling polymer brush coatings pCBAA, pCBMAA, pHPMAA, and their copolymers are not cytotoxic for Huh7 cells [ 31 ]. Here, we confirmed no cytotoxicity, even for activated and deactivated or RGD-functionalized pCB antifouling coatings.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations